Portrait of Attendees at the "Oklahoma Picnic" in Alum Rock Park - Giroux, Eugene G. (photographer):::Creator::::::::::::; Tucker, John O., d. 1928 (studio):::Contributor::::::::::::
Group portrait of men, women and children at a park. Many wear a ribbon that says "Sooner State Oklahoma Community". One man at the center of the shot holds a pitcher; another man holds a water dipper. Two automobiles are visible on the hill at the top of the photo.